Impact of Working Capital Management on Profitability of Bottler’s Nepal (Terai) Limited - Gupta, Rajan Kumar (Journal of Economics and Management, 2024)
Working capital management (WCM) is a key part of figuring out how profitable a business is because it makes sure that present assets and expenses are used efficiently. Effective WCM is important for Bottler's Nepal Terai Limited to keep their cash on hand, make the best use of their goods, and keep track of their receivables and payables. All of these things have a direct effect on their business efficiency and profit margins. How well a company balances its working capital has a big impact on its profitability, which is a key measure of its financial health. The point of this study is to look into how WCM affects earnings at Bottler's Nepal Terai Limited. This will help us understand how good financial management can improve business performance. Nine (9) years of data (from 2015 to 2023) were used for this study. They looked at data from BOTTLER'S NEPAL (TERAI) LIMITED. The data came from yearly reports and was studied with statistical tools like mean, descriptive statistics, Pearson correlation, regression analysis, multicollinearity, and F-test. SPSS 21.0 versions were used to compute and handle all of the data that was gathered. Cash conversion period (CCP), Inventor Conversion period (ICP), Receivable conversion period (RCP), and Payable delayed period (PDP) are the independent factors that make up working capital. Return on assets (ROA) is the dependent variable. The number of R-square is 0.166, which can be seen in the model report. In other words, the four independent factors can explain around 16.6% of the changes in the dependent variable. But these independent factors still can't explain 83.4% of the changes that were looked at in this study. It seems that there is a strong connection between revenue (ROA) and PDP. On the other hand, it is clear that revenue and ICP, RCP, and CCP are not significantly linked.